Formation en encadrement éducatif : quelles logiques pour quels principes ? - Chauvigné, Céline (Phronesis, 2022)
Since the 1990s, the training of teachers and principal education advisors has undergone recurrent changes that more or less transform the very meaning of the training model in question. In a socio-historical approach, we will go back to the first principles that constitute it and will try to detect the tensions, the paradoxes and the aporias in the identity construction of these professionals of education.
Publisher: Université de Sherbrooke
Keywords: Principal education advisors; conseillers principaux d’éducation; construction identitaire; ideal type; identity construction; idéal type; modèle de formation; training model